Trends of white grouper landings in the Northeastern Mediterranean: reliability and potential use for monitoring - MAVRUK, SINAN (Mediterranean Marine Science, 2020)
As a consequence of national fishery statistics showing a sharp decline in the landings of white groupers (WG), Epinephelus aeneus (Geoffroy Saint-Hilaire, 1817) after 2010, the decision to ban any further fishing of the species was implemented by the Turkish management authority in 2016. Stakeholders have since strongly objected to this decision claiming that the trends of landing statistics are unreliable. Here, this assertion is questioned using multiple sources of data. The catch per unit effort (CPUE) from the fishery independent bottom trawl survey (2004-2018) officially reported landing statistics (2002-2017) and the microdata set of landings (2012-2016) gathered by the Turkish Statistical Institute (TUIK). Based on the results of this study, there was a clear parallelism amongst the data sets. Landing records and the CPUE time series revealed unimodal non-linear patterns along the time (p<0.001). Landings increased until 2010 and decreased thereon after, whereas CPUE values started to decrease after 2009. In segmented time series, there were no statistically significant differences between the direction and magnitude of slopes of landings and fishery independent data. Cross-correlations between landings and CPUE were statistically significant with one and two-year lag distances. This was because the earlier age groups were sampled with coastal bottom trawl operations. Combined with further efforts, this finding may help to develop a monitoring program for the status of white grouper populations in the northeastern Mediterranean and contribute to a better management strategy.